Performing Communicative Language Teaching in Mandarin Mobile Learning - Chua, Nurul Ain; Soon, Goh Ying (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Students should be able to develop their communication abilities instead of just concentrating on translation methods. As a result, Communicative Teaching Language (CLT) had become the most favored approach to achieving the verbal goal as it was known as the most effective strategy to enhance learners' communicative competence. However, it was not a one-size-fits-all approach, and language instructors were advised to integrate educational technology to develop learning for students. Hence, CLT Mandarin mobile learning via personal action research was conducted to determine the extent of the approach on students' oral learning attainment, attitudes, and learners' recommendations during the learning process. The communicative task used in this study was Chatting to Mandarin Native Speakers programme. Pre- and post-oral assessments had been conducted in response to research inquiries. In verifying the reliability and validity of the study, data were triangulated through students' oral assessments, Students' Diaries, Self-Reflective Journals and Focus Group Interviews. The outcomes showed that students enjoyed the activity and improved their confidence and oral competence. Also, they suggested that there should be more language activities. The findings indicated that, when designing CLT technology-integrated projects, an instructor needed to consider students' learning preferences which make the project a success.